Mesoporous titania thin films as efficient enzyme carriers for paraoxon determination/detoxification: effects of enzyme binding and pore hierarchy in biocatalyst activity and reusability - Francica, Cynthia; Bellino, Martin Gonzalo; Soler Illia, Galo Juan de Avila Arturo; Lobnik, A. (Royal Society of Chemistry, 2014)
Fil: Francica, Cynthia. University of Maribor. Faculty of Mechanical Engineering. Centre of Sensor Technology; Eslovenia